Dynamical Analysis of Students’ Mathematics Anxiety Model with Social Support-Dependent Transition Rates - Noraniza Bahrotul Ilmi; Diesty Hayuhantika; Rini Dwi Mardiyah (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2026)
A mathematical model of mathematics anxiety incorporating social support as a parameter influencing both the spread and recovery of anxiety among students has been constructed. Previous models focus on anxiety transmission and recovery. This model differs in that the social support parameter appears explicitly in the basic reproduction number . Higher levels of social support decrease by reducing anxiety transmission and supporting recovery. In the model, there are two equilibrium points: mathematics-anxiety-free equilibrium and mathematics-anxiety-endemic equilibrium. Mathematics-anxiety-free equilibrium locally asymtotically stable if whereas if mathematics-anxiety-endemic equilibrium is locally asymtotically stable. Numerical simulations indicate that increased social support reduces the number of anxious students ( ), while the numbers of potential students and achievers students increase. The research findings suggest that stengthening social support through peer tutoring, collaborative learning, and positive feedback from lecturers can effectively reduce students’ mathematics anxiety.